Bioaccumulation of Mercury and Other Trace Elements in the Edible Holothurian Holothuria (Halodeima) atra in Relation to Gold Mining Activities in North Sulawesi, Indonesia - Tamburini, Marco; Badocco, Denis; Ercadi, Riccardo; Turicchia, Eva; Zampa, Greta; Gasparini, Fabio; Ballarin, Loriano; Guerra, Roberta; Lasut, Markus T.; Makapedua, Daisy M.; Mamuaja, Jane; Pastore, Paolo; et al. (Frontiers in Marine Science, 2022)
Artisanal and small-scale gold mines (ASGMs) have been accompanied by widespread usage of mercury amalgamation to extract gold from ores, putting Indonesia among the top three global emitters of this pollutant and posing potential risks to the marine ecosystem and human health. Although the use of mercury has been largely eliminated following the signature of the Minamata Convention on Mercury, the practice of mercury amalgamation in ASGM has persisted in several regions, including the North Sulawesi. This study assesses how on the contamination of mercury and other trace elements coming from both industrial mines and ASGMs affects marine sediments and their bioaccumulation in two tissues (body wall and guts) of the edible holothurian Holothuria (Halodeima) atra, by comparing samples collected downstream of four mining areas to four control sites in the North Sulawesi province, Indonesia. In sediments, mean concentrations of arsenic, gold, cobalt, chromium, copper, mercury, nickel, lead, antimony, and zinc were significantly higher at sites receiving mine discharges than at control sites. Downstream to gold mines, compared to control sites, significant higher concentrations of As, Au, Cr, Hg, and Ni in holothurians body walls and of As, Au, Co, Cr, Cu, Hg, Pb, Sb, Sn, and Zn in holothurians guts were found. In general, higher contaminations in sediments and tissues were found at the site near the oldest artisanal mine. Trace element levels in H. atra specimens in North Sulawesi were generally higher than those reported in other regions. In the study area, these holothurians significantly bioaccumulate Hg, As, Zn, Cd, Cu, Sn, and biota-sediment accumulation factors were higher in guts than in body walls. From an environmental and human health perspective, Hg is resulted the most concerning element in surface sediment and H. atra specimens. Based on this evidence, further studies are urgently needed to understand better the effect of mercury and other potentially toxic trace elements in marine ecosystems and food webs in mining areas both in North Sulawesi and in many still poorly investigated southeast Pacific areas.